Design Of New Student Admission System at State Vocational School 3 Empat Lawang - Iklas Iradat Sanjaya; Pahrizal; Marhalim; AR Walad Mahfuzhi (Jurnal Komputer, Informasi dan Teknologi, 2025)
The design of the new student admission system (PPDB) at SMK Negeri 3 Empat Lawang aims to improve the efficiency and effectiveness of the selection and registration process for prospective students. This system is designed to overcome frequently encountered obstacles, such as the lengthy data verification process, difficulties in data management, and the lack of transparency in the selection process. The PPDB system prototype was developed with a web-based approach to ensure accuracy, speed, and ease of access for prospective students, parents, and the school. The main features of this system include online registration, automatic data verification, real-time announcement of selection results, and an admin dashboard to monitor the entire process. With the implementation of this system, it is expected to reduce administrative workload, increase transparency, and provide a better experience for all parties involved in the PPDB process at SMK Negeri 3 Empat Lawang